Hepatitis C Virus–Infected Patients Receiving Opioid Substitution Therapy Experience Improvement in Patient-Reported Outcomes Following Treatment With Interferon-Free Regimens. (26th December 2017) - Stepanova, Maria; Thompson, Alexander; Doyle, Joseph; Younossi, Issah; de Avila, Leyla; Younossi, Zobair M
Abstract : Treatment of chronic hepatitis C with interferon-free regimens in patients who receive opiate substitution therapy results in high virologic response rates and sustained improvement in health-related quality of life and other patient-reported outcomes. Abstract: Background: There is a paucity of patient-reported outcomes (PROs) data for people undergoing hepatitis C virus (HCV) treatment who are treated with opioid substitution therapy (OST) for addiction. Methods: Patients enrolled in phase 3 clinical trials of sofosbuvir completed 4 PRO instruments—SF-36v2, FACIT-F, CLDQ-HCV, and WPAI-HCV—before, during, and after treatment. Results: A total of 8450 HCV-infected subjects were included; 4.8% (407) were receiving OST. At baseline, OST recipients had significantly ( P < .0001) lower PRO scores (by −3.5 to −15.6 on a 0–100 scale). By the end of treatment, subjects receiving pegylated interferon, ribavirin, and sofosbuvir (IFN+RBV+SOF) experienced significant decreases in PROs regardless of OST use. Subjects receiving IFN-free RBV-containing regimens had significant but smaller PRO decreases, again similar in the OST and non-OST groups. Finally, subjects treated with regimens free of both IFN and RBV (IFN/RBV-free) showed improvements in nearly all PROs during treatment, with improvements more pronounced in OST recipients. Achieving a sustained virological response for 12 consecutive weeks after treatment cessation (SVR-12) was associated with improvement of PROs in OST recipients treated with IFN/RBV-free regimens. In contrast, OST recipients who achieved SVR-12 with IFN+RBV+SOF did not have consistent PRO gains after the SVR-12. Conclusions: Receiving IFN-free regimens leads to PRO improvement during treatment and after the SVR-12, regardless of OST status. HCV-infected subjects receiving OST did not experience similar PRO improvements with IFN-containing therapy, suggesting that IFN-based therapy may be less suitable for this vulnerable population.